Large-eddy simulation of turbulent flow in a plane asymmetric diffuser by the spectral-element method - Ohlsson, Johan; Schlatter, Philipp; Fischer, Paul F.; Henningson, Dan S. (ERCOFTAC Series, 2010)
LES and no-model LES (coarse-grid DNS) have been performed of turbulent flow in a plane asymmetric diffuser by the Spectral-Element Method (SEM). Mean profile and turbulent stresses compare well to LES results from Herbst et al., however the SEM generally predicts a later (i.e. further downstream) separation. It can be concluded that the use of a high-order method is advantageous for flows featuring pressure-induced separation.
CRIS-Team Scopus Importer:2023-03-21